2011
DOI: 10.1109/tpwrd.2010.2103575
|View full text |Cite
|
Sign up to set email alerts
|

Partial-Discharge Characteristics of Free Spherical Conducting Particles Under AC Condition in Transformer Oils

Abstract: One of the major problems in the liquid insulation is the particle contamination, which can seriously degrade the withstand voltage of the insulation. The movement of conducting particles under operation voltage can generate incipient discharges that can lead to the complete failure of the insulation system during operation. The partial-discharge characteristics of the free spherical conducting particle in the quasiuniform electric field were studied in this paper in order to better explain the partial-dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The CIGRE report [6] suggested that particle identification and counting were found to be necessary procedures of condition monitoring of converter transformers. In view of the research progress of the particle effect on the breakdown of insulating oil, focus was made on the particle types [7][8][9], voltage types [10,11] particle movement [12,13] under electric field, and partial discharge [10,13] in insulating oil. Reference [7,8] observed that conducting particles affect the dielectric strength much more than insulating particles, and larger particles reduce the breakdown voltage even more significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CIGRE report [6] suggested that particle identification and counting were found to be necessary procedures of condition monitoring of converter transformers. In view of the research progress of the particle effect on the breakdown of insulating oil, focus was made on the particle types [7][8][9], voltage types [10,11] particle movement [12,13] under electric field, and partial discharge [10,13] in insulating oil. Reference [7,8] observed that conducting particles affect the dielectric strength much more than insulating particles, and larger particles reduce the breakdown voltage even more significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The AC breakdown strength of insulating oil contaminated with different copper particle concentrations was obtained. Reference [13] also investigated the motion of single steel particle in insulating oil at AC voltage and obtained the relationship between the PDs on particle and the motion of particle in insulating oil. Most publications investigated particle effect on the breakdown characteristics of insulating oil at individual AC voltage and individual DC voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The first term on the right side of equation (1) is the oil flow traction force F D expressed as equation (2) and the direction of the horizontal of oil flow. The particle movement in the horizontal direction of the oil flow is determined by F D along the horizontal direction [16].…”
Section: Forces Of Charged Metal Particles Under Flow State and Ac Comentioning
confidence: 99%
“…When charged metal particles move to the weak parts of the insulation, they may cause electric field distortion that leads to partial discharge (PD). In addition, when charged metal particles collide with electrodes, charge transfer occurs between charged metal particles and the electrodes, thereby generating PD [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation